Optical absorption study of manganese-doped Na 2O-K 2O-P 2O 5 glasses. Issue 1 (June 2021) - Jerroudi, M; Bih, L; Haddad, M; Saadoune, I
Abstract: The mixed alkali phosphate glasses with the general formula 49.95[ x Na 2 O-(1 -x )K 2 O]- 0.1MnO 2 -49.95P 2 O 5 with x=0-1mol% were prepared and characterized using the optical absorption technique. The optical absorption spectrum of each glass exhibits a single band in the region around 200-400 nm. From the ultraviolet absorption edges, the optical parameters including optical band gap and the Urbach energy were evaluated. It is interesting to note that these optical parameters are composition-dependent. The optical band gap energy (E g ) and the Urbach energy (ΔE) show the presence of a maximum and a minimum respectively around the intermediate composition x=0.5. The non-linearity behavior of the composition dependence of Eg and ΔE is a fingerprint of the mixed-alkali effect in the glasses under study.